(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The dairy industry in our country accounts for 4% of the country’s GDP and provides a source of income and livelihood to a significant proportion of country’s population. The sector currently provides income and employment to over 2 million people across the dairy value chain. The dairy farmers, who are mostly smallholder farmers, rely on local milk collection centres that manually records milk delivery transaction in some hardcopy inventory files, which are stored in their offices. These records have been susceptible to modifications and deletions by these centres to cut down on their payments to farmers. Thus, this project explores the potential use of blockchain technology in milk delivery among smallholder farmers in the rural areas in developing nations towards creating transparency, trustworthiness, and fairness in payment to these farmers. We seek to design a farmer centric blockchain based platform that ensures that farmers are protected from unscrupulous and predatory middlemen in the milk delivery chain that exploit the illiterate and the unsuspecting farmers.